PENGAMANAN PANTAI WIDURI KABUPATEN PEMALANG - M. Ilyas Muzani; Naina Haque H.; Sumbogo Pranoto; Priyo Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
The coastal erosion at Widuri beach along ± 2 km carried a relatively large impacted for public coastal areas. Waves in coastal areas resulted breakdown existing coastal protection structure and retreat of the shoreline. Coastal protection efforts to overcome these problems are reviewed based on the results of the flow simulation, waves and prediction of changes in the shoreline adapted to the existing condition using a numerical approach. Approach method performed by SMS program (Surface water Modeling System) for the simulation of flow and GENESIS (GENEralized models for SImulating Shoreline change) for the prediction simulation of shoreline changes. Earnings results from simulations program and data analysis are used as a basic design protection structure, planned coastal protection that is seawall modifications, rehabilitation the existing revetment, addition of revetment along 120 m and addition two offshore breakwater along 200 m with distance between 90 m perpendicular to wave direction at a depth of 1 m east from Widuri tourist beach.